South Slavs in Michigan - Cetinich, Daniel (Discovering the peoples of Michigan., 2003)
The South Slavs of Michigan-Slovenes, Croats, Serbs, Macedonians, and Bosnian Muslims-are a microcosm of the immigration waves of southern and eastern Europeans who came to the United States between 1880 and 1924. History has almost forgotten these immigrants, who were instrumental in developing the large urban centers of Michigan and the United States, and who specifically contributed to development of the auto industry and struck in 1913-1914 for better working conditions in the copper mines of the Upper Peninsula. While labor problems were the primary obstacles confronting Michig.